Historia de las epidemias de sarampión en Colombia: un conteo incompleto. - Amaya-Castellanos, Claudia; Ortega, Francisco; Idrovo, Álvaro J. (Biomédica: Revista del Instituto Nacional de Salud)
Measles epidemics emerged in Colombia with the arrival of Europeans during the Conquest and Colonial periods, causing the death of thousands of indigenous people. Little is known about subsequent epidemics. Here, we summarize the history of 36 measles epidemics in Colombia, focusing on the first epidemic among the Hitnü indigenous people (1964) to improve the understanding of some historical facts. Despite underreporting, major epidemics were identified in indigenous territories (16 to 18 centuries) in Salamina (1885) and Bogotá (1905-1906). It was evident that the lack of immunity had a greater impact during the Conquest and Colonial periods. Sociocultural determinants have always influenced the occurrence of epidemics, but their effects are greater after vaccines become available. Direct and structural violence have been the most important determinants of measles epidemics in the country. Currently, a global reemergence threatens Colombia.